DESIGNING RECOMMENDATIONS BASED ON VISITOR SATISFACTION USING CORRELATION, REGRESSION AND IMPORTANCE-PERFORMANCE ANALYSIS AT TANJUNG PIAI NATIONAL PARK - Muhammad Mada Novarianto; Singgih Saptadi (Industrial Engineering Online Journal, 2026)
Tanjung Piai National Park is a park located at the southernmost point of mainland Asia in Johor, Malaysia. It possesses significant ecological and cultural value through its unique mangrove ecosystems, biodiversity, and geographical landmark status; however, despite these assets, the park has struggled with persistently stagnant visitor numbers, a narrow demographic base, and deteriorating physical infrastructure, all of which threaten its long-term viability as both a conservation site and an ecotourism destination. Previous studies have primarily focused on ecological and community-based aspects of the park. This study aims to measure visitor satisfaction across five ecotourism dimensions, based on a previous study by Anh Toai Le which are Destination Attraction, Ecotourism Services, Staff Quality, Price Fairness, and Infrastructure in order to measure and evaluate how each dimension influences visitors' willingness-to-visit, and produce a prioritized, data-driven set of management recommendations. A quantitative survey-based methodology was employed, distributing Likert-scale structured questionnaires both online and on-site to a total of 527 unique respondents, with data analyzed through Pearson correlation analysis, multiple linear regression, and Importance–Performance Analysis (IPA). The results revealed that Destination Attraction (β = 0.398) and Infrastructure (β = 0.339) are the strongest predictors of willingness-tovisit, collectively with all five dimensions explaining approximately 59.2% of the variance in revisit intention (R² = 0.592); the IPA matrix further identified Ecotourism Services as the sole dimension in the "Concentrate Here" quadrant, exhibiting a 0.70-point gap between visitor importance ratings (4.20) and actual performance ratings (3.50). Based on these findings, it is recommended that management prioritize the immediate improvement of interpretive signage, educational materials, and guided tour quality to close the Ecotourism Services gap, while sustaining scheduled maintenance of boardwalks, safety railings, and the Southernmost Tip landmark to preserve current strengths; future research should also employ more rigorous sampling strategies, incorporate international visitor perspectives, and adopt longitudinal designs to track the effectiveness of implemented improvements over time.